2019
DOI: 10.1088/1361-6528/ab3baa
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis and photocatalytic activity of butterfly-like CaTiO3 dendrites with dominant {101} facets

Abstract: Novel butterfly-like CaTiO 3 dendrites dominantly bounded by {101} facets have been synthesized via a conventional hydrothermal by using tetramethylammonium hydroxide (TMAH) as a mineralizer and surface modifier. The wing-branches of the butterfly-like CaTiO 3 dendrites are composed of primary block tetragonal plates with dominant {101} facets overlapping and ranking around the stem of 〈131〉 directions in the same plane belonging to the group of {101}. With the basis of the experimental results and the lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The butterfly like dendritic structures showed 4 times higher activity in comparison to the microcuboid structure, which was attributed to the exposed facets in the former. 174 CaTiO 3 nanospheres 175 and nanocuboids 176 are also reported for MB and RhB degradation, respectively. These reports convey that the morphology has a great impact on the photocatalytic performance of CaTiO 3 .…”
Section: Energy and Environmental Applicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…The butterfly like dendritic structures showed 4 times higher activity in comparison to the microcuboid structure, which was attributed to the exposed facets in the former. 174 CaTiO 3 nanospheres 175 and nanocuboids 176 are also reported for MB and RhB degradation, respectively. These reports convey that the morphology has a great impact on the photocatalytic performance of CaTiO 3 .…”
Section: Energy and Environmental Applicationsmentioning
confidence: 92%
“…Recently, Chen et al have reported the butterfly and microcuboid CaTiO 3 morphologies and studied their performance toward photocatalytic degradation of Rhodamine B (RhB) under UV light irradiation. The butterfly like dendritic structures showed 4 times higher activity in comparison to the microcuboid structure, which was attributed to the exposed facets in the former . CaTiO 3 nanospheres and nanocuboids are also reported for MB and RhB degradation, respectively.…”
Section: Energy and Environmental Applicationsmentioning
confidence: 92%